Study on shareholders activism and it's implication on governance disclosure of minority shareholders information / Fadzlina Mohd Fahmi - Mohd Fahmi, Fadzlina (2002)
Shareholder activism is a new scenario in this country. The government has done a lot of efforts in order to promote this activity. It is one of corporate governance mechanism which involves shareholders. Hence, they are expected to play their role in order to promote good corporate governance practice. In order for shareholder to play active role in corporate governance, they must have knowledge of their basic roles and rights. In fact, they should know how to play their active role when attending the company's annual general meeting. Shareholders should know that, they have a direct access to directors when they attend the companies' annual general meeting and may questions directors in relation to various issues on the company. However, the most worrying phenomena are that shareholders do not bother to attend the annual general meeting and also to exercise voting rights. If this continues, shareholders activism remains as a myth in this country. Thus, this paper is aimed to address shareholders awareness of their roles and rights and provide reasons behind shareholders non-participation in the annual general meeting. Based on the findings, it was found that shareholders are not aware or being ignorant of their roles and rights. Further, shareholders claimed that their small shareholding is the important reason for their non-participation in the annual general meeting. Investors also revealed a few factors that would encourage them to attend the annual general meeting. Some of the factors are time availability, value added as an investor, knowledge on shareholders rights, agenda of the meeting, knowledge and types of issues to be addressed during the meeting.